Interstitial Cystitis/Bladder Pain Syndrome - Marcu, Ioana; Campian, E. Cristian; Tu, Frank F. (Seminars in Reproductive Medicine, 2018)
Interstitial cystitis/bladder pain syndrome is an uncommon but potentially devastating pelvic pain disorder affecting both women and men. This condition is often confusable and comorbid with other pelvic pain disorders. Although our understanding of the underlying pathophysiology is growing, the exact longitudinal course by which peripheral and central aberrations involving the bladder mucosa, peripheral inflammation, and central dysregulation of bladder sensitivity create painful bladder symptoms remains an area in need of further study. Only a limited number of drugs have been approved for treatment by the Food and Drug Administration, and overall durable efficacy of the many treatments reviewed in recent American Urological Association guidelines remains suboptimal, making awareness, early diagnosis, and use of effective treatments early in the disease course, where neural changes may still be reversible, imperative.
Keywords: chronic overlapping pain conditions; cross-organ sensitization; glycosaminoglycan layer